Daily field checking list by Walter Rosene, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist. This checklist was used by Walter Rosene to record the bird species he sighted during 1933. Plustek--flatbed